Selaginella P. Beauv. from Minas Gerais, Brazil - Gustavo Heringer (Acta Botânica Brasílica, 2016)
Selaginella P. Beauv. is the only genus in the family Selaginellaceae Willk. The genus is monophyletic, has a cosmopolitan distribution, contains about 750 species and can be characterized by the presence of rhizophores, leaves, a ligule, heterospory and adaxial, reniform sporangia. Twenty species were found in the study area: Selaginella alstonii, S. contigua, S. convoluta, S. decomposita, S. erectifolia, S. erythropus, S. flexuosa, S. jungermannioides, S. macrostachya, S. marginata, S. microphylla, S. muscosa, S. producta, S. sellowii, S. sematophylla, S. suavis, S. sulcata, S. tenella, S. tenuissima and S. vestiens. Two new species records for the state are presented (S. jungermannioides and S. tenella). We present descriptions of the genus and species, an identification key, the synonyms pertaining to Brazil, illustrations, and comments about the taxonomy and distribution of species in Brazil.